PENGARUH KOMUNIKASI POLITIC ENTERTAINMENT MELALUI IKLAN TERHADAP TINGKAT KETERPILIHAN PARTAI POLITIK PADA PEMILIHAN UMUM 2019 - Muhamad Ferdy Firmansyah (Jurnal Gama Societa, 2019)
Globalization demands the development of communication media, which is TV advertisment. Indonesian political dynamics is one of the most unique and fresh studies discussed in various perspectives. It concerns ondecision making and ethical political differentiation that empirically influences the political legitimacy in political representation. Digital politics is very popular within the society it could be categorized as swing voters. Digital politic is growing close to the 2019 general election as the effort of low politics tendencies that can be analyzed using the cultural value. Political parties have a polarization to use TV advertisement to be a media for socialization their political goals. The implementation of this style is usually called politics entertainment. This research explains the influence of digital political style and entertainment politics with TV advertisement on the level of electability of political parties in the general election 2019 through data interpretation method. The research is conducted as a means to explain the understanding ofmass polarization in online setting. Additionally, it is also purposed to know the effectiveness of digital politics and entertainment politics in its use in the 2019 general election.